Effects of environmental enrichment and lack of beak trimming on aspects of health, behaviour and production of commercial turkeys - Josiane G. Busatta; Luciana Foppa; Jhonatan Sperandio; Daniele S. Martins; Cristiane G. Titto (Spanish Journal of Agricultural Research)
Aim of study: The purpose of this study was to verify whether the insertion of a pecking object as an environmental enrichment (EE) would be sufficient to prevent the beak trimming (BT) process in turkeys. Area of study: Southern Brazil. Material and methods: A total of 3,116 female turkeys of the Nicholas Super Select line were equally distributed across four treatments in a 2 × 2 factorial scheme with the presence or absence of EE and BT or intact beak. The turkeys were housed at a density of 21 kg/m2 and were followed-up for 62 days until slaughter. Each week, the behaviour of the turkeys, body lesions, and performance indicators such as mortality, feed conversion, feed consumption, and weight were evaluated. Main results: The results regarding injuries and performance showed, in most cases, better results for beak trimmed animals (p>0.05). The addition of EE was not effective in reducing the number of injuries in either debeaked or non-debeaked turkeys (p>0.05). Injurious pecking of turkeys may result from vigorous investigative pecking. Research highlights: We can conclude that debeaking decreases the number of aggressive injuries in animals, and further research needs to be conducted to search for a possible alternative to EE to avoid BT, reduce injuries, and enhance performance.